The animal behaviour collective: building confidence and breaking barriers through community - Delphine De Moor; Stotra Chakrabarti; Diana da Silva; Catherine Hobaiter; Nicola Khan; Emma Suvi McEwen; Hella Péter; Zakhiya Pulukkol Cheriyandintakath; Sharmi Sen; Ashwin Suryanarayanan; Chelsea J. Thompson; Jessica E.M. van der Wal; et al. (Animal Behaviour, 2026)

Residual waste after achieving organic diversion targets: Will nappies (diapers) spoil the plan? - Emma Thompson Brewster; William Clarke (Waste Management, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Simulation of the Hydro-ecological Impacts of Climate Change on an Upland Peatland in the Massif Central - Julian Richard Thompson; Arnaud Duranel; Emma Keisser; Philippe Durepaire; Hervé Cubizolle (Wetlands, 2026)
Hydro-ecological impacts of 60 climate change scenarios on peat ecosystems of the Dauges National Nature Reserve are assessed using high spatial resolution MIKE SHE / MIKE 11 modelling. Annual precipitation increases for 45 of 60 scenarios (ensemble mean increases: 5–8% for RCP2.6, 1–5% for RCP8.5). Annual potential evapotranspiration increases in all cases (ensemble mean: 2–3% for RCP2.6, 6–12% for RCP8.5). Winters become wetter and summers drier. Mean stream discharges increase in most cases (ensemble means for catchment outlet: 8–9% for RCP2.6, 2–4% (2050s) and − 1–2% (2080s) for RCP8.5). Flows become more seasonal with increasing peaks and declining lows. Winter peat groundwater levels still intercept the surface but declines in summer dominate (> 80% of cases) driving enhanced seasonal ranges and lower mean levels (> 70% of cases). The magnitude of changes increases with higher radiative forcing and into the future (ensemble mean increases in low levels of <1 cm for RCP2.6 in both time slices, declines of 5–7 cm and 12–14 cm for RCP8.5 in the 2050s and 2080s, respectively). The largest declines are concentrated around peatland margins. Hydrological conditions assumed to support mire vegetation decline in extent in most cases (41 of 60 scenarios, more common with higher radiative forcing). Small (< 1%) increases in area are projected by ensemble means for RCP2.6 with declines of 12–13% for RCP8.5 in the 2080s. Sources of uncertainty include shifts in catchment vegetation, changes in peat hydraulic properties and mire vegetation species-specific impacts of hydrological changes.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

How to understand the psychological drivers of household food waste - Katy Tapper; Bethan Thompson; Christian Reynolds; Rosie Morrison; Emma Leask; Luiza Toma (Appetite, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Global vegetation zonation and terrestrial climate of the warm Early Eocene - Nick Thompson; Ulrich Salzmann; David K. Hutchinson; Stephanie L. Strother; Matthew J. Pound; Torsten Utescher; Julia Brugger; Thomas Hickler; Emma P. Hocking; Daniel J. Lunt (Earth-Science Reviews, 2025)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Association between pre-diagnosis recreational physical activity and risk of breast cancer recurrence: the California Teachers Study - Dan Lin; Cheryl L. Thompson; Alaina Demalis; Rebecca Derbes; Laila Al-Shaar; Emma S. Spielfogel; Kathleen M. Sturgeon (Cancer Causes & Control, 2024)

Development of a 5-HT7 receptor antibody for the rat: the good, the bad, and the ugly - Janice M. Thompson; Will Tragge; Emma D. Flood; Stefan Schulz; Erika Lisabeth; Stephanie W. Watts (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Our laboratory has a vested interest in measuring the location and expression of the 5-hydroxytryptamine (5-HT, serotonin) 7 (5-HT 7 ) receptor in the rat. Determining tissue-specific receptor expression would aid in validating understood and potentially new tissues that support the 5-HT 7 receptor-mediated fall in blood pressure, an event we are committed to understand. We contracted with 7TM Antibodies to develop deliberately and rigorously a rat 5-HT 7 (r5-HT 7 ) receptor specific antibody. Three antigens, two targeting the third internal loop and one the C terminus, were used in three rabbits to generate antibodies. As a positive control, HEK293(T or AD) cells were transfected with a plasmid for the r5-HT 7 receptor also expressing a C terminus 3xFLAG tag. Naïve rat tissues were also used in Western and immunohistochemical analyses. Nine antibodies (3 from three different rabbits) detected a ~ 75 kDa protein absent in homogenates of vector control HEK293T cells. Only antibodies that recognized the C terminus of the 5-HT 7 receptor [ERPERSEFVLQNSDH(Abu)GKKGHDT; antibodies 3, 6, and 9] positively and concentration-dependently identified the r5-HT 7 receptor expressed in Westerns of transfected HEK293T cells. These same C terminus antibodies also successfully detected the r5-HT 7 receptor in immunocytochemical test of the transfected HEK293AD cells, colocalizing with the detected FLAG sequence. In naive tissue, antibody 6 performed the best, identifying specific bands in the brain cortex in Western analysis. These same antibodies produced a more diverse band profile in the vena cava, identifying 6 major proteins. In immunohistochemical experiments, the same C-terminus antibodies, with antibody 3 performing the best, detected the 5-HT 7 receptor in rat veins. This deliberate work has given rise to at least three antibodies that can be used with good confidence in r5-HT 7 transfected cells, two antibodies that can be used in immunohistochemical analyses of rat tissues and in Westerns of rat brain; we are less confident of the use of these same antibodies in rat veins.

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Transitions in modes of coastal adaptation: addressing blight, engagement and sustainability - Sally Brown; Emma L. Tompkins; Natalie Suckall; Jon French; Ivan D. Haigh; Eli Lazarus; Robert J. Nicholls; Edmund C. Penning-Rowsell; Charlie E. L. Thompson; Ian Townend; Sien van der Plank (Frontiers in Marine Science, 2023)
Coastal defences have long provided protection from erosion and flooding to cities, towns and villages. In many parts of the world, continued defence is being questioned due to both environmental, sustainability and economic considerations. This is exemplified in England and Wales, where strategic Shoreline Management Plans envisage realignment of many protected coasts, often with low population densities, over the coming decades. The policy transition from protection to realignment is often resisted by affected communities and can have high political costs. Whilst some preparations for such transitions have been made, the communities affected are often not fully aware of the implications of policy change, and this brings the potential for blight. In this paper, we investigate the challenges of implementing transitions in coastal policy within England and Wales. The analysis is based on data obtained from three workshops held in 2019 that were attended by council members, engineers, planners, scientists and other relevant professionals. Five conditions are found to promote contention: (i) policy actors with competing priorities and different decision making time frames (immediate to decadal to a century); (ii) divergence between regulations and ad hoc political decisions (e.g. in relation to the demand for new housing); (iii) limited or non-existent funding to support policy transition; (iv) community expectation that protection is forever; and (v) a disconnection between people and ongoing coastal change. Our research indicates that transitions can be better supported through: (1) integrated multi-scalar preparedness for coastal change; (2) an accessible evidence base and future vision to nurture political confidence in adaptation; and (3) defined, time-bound and accessible diverse funding streams to achieve transitions. Critically, these generic actions need to be embedded within the local political and planning system to facilitate transition to more sustainable coasts and their communities.

A National-Level Assessment of Lemur Hunting Pressure in Madagascar - Cortni Borgerson; Steig E. Johnson; Emma Hall; Kerry A. Brown; Pamela R. Narváez-Torres; Be Jean Rodolph Rasolofoniaina; Be Noel Razafindrapaoly; Samuel D. Merson; Katharine E. T. Thompson; Sheila M. Holmes; Edward E. Louis; Christopher D. Golden (International Journal of Primatology, 2022)

Evaluation of pharmacogenomics and hepatic nuclear imaging–related covariates by population pharmacokinetic models of irinotecan and its metabolites - Zheng Liu; Jennifer H. Martin; Winston Liauw; Sue-Anne McLachlan; Emma Link; Anetta Matera; Michael Thompson; Michael Jefford; Rod J. Hicks; Carleen Cullinane; Athena Hatzimihalis; Ian Campbell; et al. (European Journal of Clinical Pharmacology, 2022)

Holosteans contextualize the role of the teleost genome duplication in promoting the rise of evolutionary novelties in the ray-finned fish innate immune system - Alex Dornburg; Dustin J. Wcisel; Katerina Zapfe; Emma Ferraro; Lindsay Roupe-Abrams; Andrew W. Thompson; Ingo Braasch; Tatsuya Ota; Jeffrey A. Yoder (Immunogenetics, 2021)

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

A double pedigree reveals genetic but not cultural inheritance of cooperative personalities in wild banded mongooses - Hazel J. Nichols; Kevin Arbuckle; Jennifer L. Sanderson; Emma I. K. Vitikainen; Harry H. Marshall; Faye J. Thompson; Michael A. Cant; David A. Wells (Ecology Letters, 2021)
Personality traits, such as the propensity to cooperate, are often inherited from parents to offspring, but the pathway of inheritance is unclear. Traits could be inherited via genetic or parental effects, or culturally via social learning from role models. However, these pathways are difficult to disentangle in natural systems as parents are usually the source of all of these effects. Here, we exploit natural ‘cross fostering’ in wild banded mongooses to investigate the inheritance of cooperative behaviour. Our analysis of 800 adult helpers over 21 years showed low but significant genetic heritability of cooperative personalities in males but not females. Cross fostering revealed little evidence of cultural heritability: offspring reared by particularly cooperative helpers did not become more cooperative themselves. Our results demonstrate that cooperative personalities are not always highly heritable in wild, and that the basis of behavioural traits can vary within a species (here, by sex).

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

A global analysis of complexity–biodiversity relationships on marine artificial structures - Elisabeth M. A. Strain; Peter D. Steinberg; Maria Vozzo; Emma L. Johnston; Marco Abbiati; Moises A. Aguilera; Laura Airoldi; J. David Aguirre; Gail Ashton; Maritina Bernardi; Paul Brooks; Benny K. K. Chan; et al. (Global Ecology and Biogeography, 2021)
Aim Topographic complexity is widely accepted as a key driver of biodiversity, but at the patch‐scale, complexity–biodiversity relationships may vary spatially and temporally according to the environmental stressors complexity mitigates, and the species richness and identity of potential colonists. Using a manipulative experiment, we assessed spatial variation in patch‐scale effects of complexity on intertidal biodiversity. Location 27 sites within 14 estuaries/bays distributed globally. Time period 2015–2017. Major taxa studied Functional groups of algae, sessile and mobile invertebrates. Methods Concrete tiles of differing complexity (flat; 2.5‐cm or 5‐cm complex) were affixed at low–high intertidal elevation on coastal defence structures, and the richness and abundance of the colonizing taxa were quantified after 12 months. Results The patch‐scale effects of complexity varied spatially and among functional groups. Complexity had neutral to positive effects on total, invertebrate and algal taxa richness, and invertebrate abundances. However, effects on the abundance of algae ranged from positive to negative, depending on location and functional group. The tidal elevation at which tiles were placed accounted for some variation. The total and invertebrate richness were greater at low or mid than at high intertidal elevations. Latitude was also an important source of spatial variation, with the effects of complexity on total richness and mobile mollusc abundance greatest at lower latitudes, whilst the cover of sessile invertebrates and sessile molluscs responded most strongly to complexity at higher latitudes. Conclusions After 12 months, patch‐scale relationships between biodiversity and habitat complexity were not universally positive. Instead, the relationship varied among functional groups and according to local abiotic and biotic conditions. This result challenges the assumption that effects of complexity on biodiversity are universally positive. The variable effect of complexity has ramifications for community and applied ecology, including eco‐engineering and restoration that seek to bolster biodiversity through the addition of complexity.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

Human-specific RNA analysis shows uncoupled epithelial-mesenchymal plasticity in circulating and disseminated tumour cells from human breast cancer xenografts - Anthony Tachtsidis; Anh Viet-Phuong Le; Tony Blick; Devika Gunasinghe; Emma De Sousa; Mark Waltham; Alex Dobrovic; Erik W. Thompson (Clinical & Experimental Metastasis, 2019)

Linking climate variability and growth in coral skeletal records from the Great Barrier Reef - Emma V. Reed; Julia E. Cole; Janice M. Lough; Diane Thompson; Neal E. Cantin (Coral Reefs, 2019)

Intragroup competition predicts individual foraging specialisation in a group‐living mammal - Catherine E. Sheppard; Richard Inger; Robbie A. McDonald; Sam Barker; Andrew L. Jackson; Faye J. Thompson; Emma I. K. Vitikainen; Michael A. Cant; Harry H. Marshall (Ecology Letters, 2018)
Individual foraging specialisation has important ecological implications, but its causes in group‐living species are unclear. One of the major consequences of group living is increased intragroup competition for resources. Foraging theory predicts that with increased competition, individuals should add new prey items to their diet, widening their foraging niche (‘optimal foraging hypothesis’). However, classic competition theory suggests the opposite: that increased competition leads to niche partitioning and greater individual foraging specialisation (‘niche partitioning hypothesis’). We tested these opposing predictions in wild, group‐living banded mongooses ( Mungos mungo ), using stable isotope analysis of banded mongoose whiskers to quantify individual and group foraging niche. Individual foraging niche size declined with increasing group size, despite all groups having a similar overall niche size. Our findings support the prediction that competition promotes niche partitioning within social groups and suggest that individual foraging specialisation may play an important role in the formation of stable social groupings.

Transcriptomic profiling of adaptive responses to ocean acidification - Priscila Goncalves; David B. Jones; Emma L. Thompson; Laura M. Parker; Pauline M. Ross; David A. Raftos (Molecular Ecology, 2017)
Some populations of marine organisms appear to have inherent tolerance or the capacity for acclimation to stressful environmental conditions, including those associated with climate change. Sydney rock oysters from the B2 breeding line exhibit resilience to ocean acidification ( OA ) at the physiological level. To understand the molecular basis of this physiological resilience, we analysed the gill transcriptome of B2 oysters that had been exposed to near‐future projected ocean pH over two consecutive generations. Our results suggest that the distinctive performance of B2 oysters in the face of OA is mediated by the selective expression of genes involved in multiple cellular processes. Subsequent high‐throughput qPCR revealed that some of these transcriptional changes are exclusive to B2 oysters and so may be associated with their resilience to OA . The intracellular processes mediated by the differentially abundant genes primarily involve control of the cell cycle and maintenance of cellular homeostasis. These changes may enable B2 oysters to prevent apoptosis resulting from oxidative damage or to alleviate the effects of apoptosis through regulation of the cell cycle. Comparative analysis of the OA conditioning effects across sequential generations supported the contention that B2 and wild‐type oysters have different trajectories of changing gene expression and responding to OA . Our findings reveal the broad set of molecular processes underlying transgenerational conditioning and potential resilience to OA in a marine calcifier. Identifying the mechanisms of stress resilience can uncover the intracellular basis for these organisms to survive and thrive in a rapidly changing ocean.

Erratum to: Trends in the classical biological control of insect pests by insects: an update of the BIOCAT database - Matthew J. W. Cock; Sean T. Murphy; Moses T. K. Kairo; Emma Thompson; Rebecca J. Murphy; Antonio W. Francis (BioControl, 2017)

Demography and ecology of southern right whales Eubalaena australis wintering at sub-Antarctic Campbell Island, New Zealand - Leigh G. Torres; Will Rayment; Carlos Olavarría; David R. Thompson; Brittany Graham; C. Scott Baker; Nathalie Patenaude; Sarah Jane Bury; Laura Boren; Graham Parker; Emma L. Carroll (Polar Biology, 2017)

Rapid transcriptional acclimation following transgenerational exposure of oysters to ocean acidification - Priscila Goncalves; Kelli Anderson; Emma L. Thompson; Aroon Melwani; Laura m. Parker; Pauline M. Ross; David A. Raftos (Molecular Ecology, 2016)
Marine organisms need to adapt in order to cope with the adverse effects of ocean acidification and warming. Transgenerational exposure to CO 2 stress has been shown to enhance resilience to ocean acidification in offspring from a number of species. However, the molecular basis underlying such adaptive responses is currently unknown. Here, we compared the transcriptional profiles of two genetically distinct oyster breeding lines following transgenerational exposure to elevated CO 2 in order to explore the molecular basis of acclimation or adaptation to ocean acidification in these organisms. The expression of key target genes associated with antioxidant defence, metabolism and the cytoskeleton was assessed in oysters exposed to elevated CO 2 over three consecutive generations. This set of target genes was chosen specifically to test whether altered responsiveness of intracellular stress mechanisms contributes to the differential acclimation of oyster populations to climate stressors. Transgenerational exposure to elevated CO 2 resulted in changes to both basal and inducible expression of those key target genes (e.g. ec SOD , catalase and peroxiredoxin 6), particularly in oysters derived from the disease‐resistant, fast‐growing B2 line. Exposure to CO 2 stress over consecutive generations produced opposite and less evident effects on transcription in a second population that was derived from wild‐type (nonselected) oysters. The analysis of key target genes revealed that the acute responses of oysters to CO 2 stress appear to be affected by population‐specific genetic and/or phenotypic traits and by the CO 2 conditions to which their parents had been exposed. This supports the contention that the capacity for heritable change in response to ocean acidification varies between oyster breeding lines and is mediated by parental conditioning.

Trends in the classical biological control of insect pests by insects: an update of the BIOCAT database - Matthew J. W. Cock; Sean T. Murphy; Moses T. K. Kairo; Emma Thompson; Rebecca J. Murphy; Antonio W. Francis (BioControl, 2016)

Towards improving the framework for probabilistic forecast evaluation - Leonard A. Smith; Emma B. Suckling; Erica L. Thompson; Trevor Maynard; Hailiang Du (Climatic Change, 2015)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)